Fuzzy approach for student's performance analyzer / Mohd Iqbal Radzuan - Radzuan, Mohd Iqbal (Faculty of Computer and Mathematical Sciences, 2007)
As it is a routine activity, the tedious and dreary process of evaluating student's academic records will be a problem for academic advisor to recognize their student's intelligence ability in academic. This major difficulty leads to ineffective evaluation of student's academic records which have to consider many criteria in order to analyze them. Sometimes, it could resuh to unreliable analyzed result. The objective of this research is to apply the concept of fuzzy logic and fuzzy inferencing in Howard Gardner's tiieory of multiple intelligence in order to determine student's intelligence level. Concept of fuzzy logic and fuzzy inferencing is proved to be well suited to the problem of this nature as it is capable of capturing the imprecision of human reasoning and judgments. These two concepts have been implemented in the prototype of Student's Performance Analyzer. The prototype is enable to assist academic advisor by analyze the student's academic record and determine their intelligence level in three different areas: spatial, logic and arithmetic, and linguistic. The prototype also is able to provide efficient and reliable analyzing result compared to human's analyzing process. As for the recommendation, the decision support system is one of the enhancement solutions to the research by combining concept of fiizzy logic, fazzy inferencing and decision support system architecture.